Why does the young generation invest in sharia mutual funds on the Bibit platform? - Deni Lubis; Kurnia Tri Wahyuni; Yekti Mahanani; Aditya Hadad Riyadi (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This study aims to examine the factors that affect the younger generation's use of the Bibit platform to invest in sharia mutual funds.Methodology – This study relies on primary data from 300 people aged 17 to 40 who used the Bibit platform to invest in sharia mutual funds and the study used Structural Equation Modelling Partial Least Squares (SEM-PLS) to analyze the relationship between independent variables and dependent variables using the SmartPLS 3.2.9 application. Data transformation is supported by Microsoft Excel 2019 and IBM SPSS Statistics 25.Finding – It has been discovered that a variety of factors, including behavioral goals, social influence, attitudes toward use, perceived risks, and perceived rewards all have an impact on whether or not the young generation uses the Bibit platform for investing in Islamic mutual funds.Implication – This research will assist stakeholders in developing strategies and policies to increase demand for sharia instruments among the younger generation.Originality – Indonesia's population is dominated by the younger generation who are the main potential investors in the future. This research contributes to attracting young investors to invest in Islamic mutual funds in Indonesia so that Islamic finance is increasingly developed.